Profil Fisik, Kimia dan Biologi Pupuk Organik Cair Ampas Teh - Rahmiati Rahmiati; Helen Anjelina Simanjuntak; Toberni S Situmorang; Hayyu Nisa Abdillah; Vera Novita Manalu; Deswita Asriani Tanjung (Herbal Medicine Journal, 2026)
Tea waste is an organic by-product that still contains essential nutrients and organic compounds, making it a promising raw material for the production of liquid organic fertilizer (LOF). This study aimed to evaluate the physical, chemical, and biological characteristics of LOF produced through the fermentation of tea waste. A quantitative descriptive method was employed using a seven-day fermentation process. The evaluated parameters included physical characteristics (color, odor, and pH), chemical properties (organic carbon, total nitrogen, and C/N ratio), and biological characteristics based on the total bacterial count. The results showed that the resulting LOF was dark brown in color, exhibited a characteristic tea aroma with a distinct acidic odor due to fermentation, and had a pH of 5.5. These physical characteristics complied with the quality requirements for liquid organic fertilizer stipulated in the Indonesian Ministry of Agriculture Regulation No. 70 of 2011. Chemical analysis revealed an organic carbon content of 9.8%, a total nitrogen content of 0.75%, and a C/N ratio of 13.06. The relatively low C/N ratio indicated that the fermentation process had proceeded effectively and that the produced LOF had reached an adequate level of maturity. This finding was supported by the total bacterial count of 6.56 × 10⁸ CFU mL⁻¹, indicating active microbial growth during the fermentation process. Overall, tea waste has considerable potential as a raw material for producing liquid organic fertilizer and may contribute to sustainable organic waste management practices